DIVERSITY, AFFINITIES AND ADAPTATIONS OF THE SOUTH AMERICAN BASAL SPARASSODONT PATENE SIMPSON, 1935 (MAMMALIA, METATHERIA) (Ameghiniana, 2019)
The sparassodonts were the main mammalian predators during most of Cenozoic in South America. The lower Eocene Itaboraí Basin/Formation includes the second oldest fossil records of this group in South America: Patene and Nemolestes. Patene is by far the most abundant sparassodont from this formation, with more than 30 specimens referable to a single taxon, Patene simpsoni. Some specimens recovered from the Quebrada de Los Colorados Formation (former Lumbrera Formation – middle Eocene) in Northwestern Argentina have been also referred to P. simpsoni. In order to test the affinities of Patene and the taxonomy of the Argentinean specimens, we performed a review of the genus. We concluded that the specimens from Northwestern Argentina show significant differences from the Brazilian specimens: smaller size, paraconid more developed; metaconid, entoconid and hypoconid more reduced. As a result, the specimens from the Quebrada de Los Colorados Formation were assigned to a new species, Patene coloradensis. Our phylogenetic analysis supported previous hypotheses that exclude Patene from the “Hathliacynidae”, as the former was recovered as an earlier divergent lineage. The results also supported the hypothesis that Allqokirus australis and Mayulestes ferox from the Tiupampa Basin (El Molino Formation, lower Paleocene – Tiupampian), Bolivia, are the oldest known representatives of the Sparassodonta. The results also supported the monophyly of the Pucadelphyida with the inclusion of the Jaskhadelphyidae and closely related taxa in addition to the Pucadelphyidae + Sparassodonta. The Late Cretaceous, North American Varalphadon was not recovered in our phylogenetic analysis as a representative of the Sparassodonta.Based on our results, the Sparassodonta should be considered, based on the current fossil record, as a South American endemic lineage.doi: 10.5710/AMGH.06.05.2019.3222